Handover Of Printers As An Effort To Improve Administrative Support Facilities For Teachers And Students At Al-Azhar Private High School, Batam - Dailami; Pratama, Tito; Alhamdi, Rezki; Thamdzir, Moh.; Sipayung, Natal Olotua; Rais, Syafruddin; Maldin, Siska Amelia; Ilham, Wahyudi; Irwansyah R, Syailendra Reza; Sukmamedian, Haufi; Yusuf, Abd Rahmad (JURNAL KEKER WISATA, 2026)
This community service activity aims to improve administrative support facilities at Al-Azhar Private High School Batam through the delivery of printers as a form of support for teaching and learning activities and school administration management. The problem faced by the school is the limited document printing facilities which has an impact on delays in the administrative process and the preparation of academic reports. Through this activity, the PKM implementation team coordinates with the school to distribute assistance in the form of a multifunctional printer unit that can be used by teachers and students in supporting administrative and academic activities. The implementation method includes a needs survey, equipment handover, and short training on the use of printers effectively and efficiently. The results of the activity show that the addition of this facility has a positive impact on the smooth school administration process, increases the efficiency of teachers' working time, and makes it easier for students to print learning documents. With this activity, it is hoped that it can strengthen cooperation between higher education institutions and high schools in an effort to improve the quality of education.